Beta-alanine supplementation enhances judo-related performance in highly-trained athletes - Kratz, C.; Painelli, V.; Nemezio, K.; Silva, R.; Franchini, E.; Zagatto, A.; Gualano, B.; Artioli, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In official judo competitions, athletes have to engage in 5-7 matches in the same day (Detanico et al. 2015), during which they perform numerous high-intensity efforts interspersed by short recovery intervals. Thus, glycolytic demand in judo is high and acidosis may limit performance (Artioli et al. 2010). Carnosine is a relevant intracellular acid buffer whose content is increased with beta-alanine supplementation (Harris et al. 2006). Thus, we hypothesized that beta-alanine supplementation could attenuate acidosis and improve judo performance. Methods: Twenty-three highly-trained judo athletes were randomly assigned to receive either beta-alanine (6.4 g.day-1; n=12; age=19 ± 3 y) or placebo (dextrose, 6.4 g.day-1; n=11; age=17±2 y). Performance was assessed before (PRE) and after (POST) supplementation through a 5-minute simulated fight (randori) followed by 3 bouts of the Special Judo Fitness Test (SJFT) (Sterkowicz et al. 2010). Blood samples were collected for blood pH, bicarbonate (HCO3-) and lactate determination. Results: Beta-alanine supplementation significantly improved the number of throws per set, as well as the total number of throws (both P < 0.05), whilst placebo did not change these variables (both P > 0.05). Blood pH and HCO3- were significantly reduced after exercise (all P < 0.001), with no between-group differences (all P > 0.05). However, the lactate responses to exercise were higher in the beta-alanine group as compared to placebo (P < 0.05). Discussion: The likely elevated muscle buffering capacity has probably attenuated muscle acidosis during the judo-specific protocol, thereby allowing for enhanced glycolytic activation and better performance. In conclusion, 4 weeks of beta-alanine supplementation is an effective dietary intervention capable of enhancing judo-related performance in well-trained judo athletes, suggesting that this modality can also benefit from the ergogenic effects of an increased muscle carnosine content.